Wealth inequality and utilization of reproductive health services in the Republic of Vanuatu: insights from the multiple indicator cluster survey, 2007 - Rahman Mosiur; Haque Syed E; Mostofa Md G; Tarivonda Len; Shuaib Muhammad (BMC, 2011)
Abstract Background Although the Republic of Vanuatu has improved maternal indicators, more needs to be done to improve equity among the poorest in the use of reproductive health services to expedite the progress towards the Millennium Development Goal 5(MDG 5) target. While large developing country studies provide evidence of a rich-poor gap in reproductive health services utilization, not much is written in terms of Pacific Islands. Thus, this study aims to examine the degree of inequality in utilization of reproductive health services in a nationally representative sample of Vanuatu households. Methods This paper used data from the 2007 Vanuatu Multiple Indicator Cluster Survey (MICS). The analyses were based on responses from 615 ever married women, living with at least one child below two years of age. Outcomes included antenatal care (ANC) and use of birth attendants at delivery, place of delivery, and counseling and testing for HIV/AIDS. Descriptive statistics and multivariate logistic regression methods were employed in the analysis. Results Findings revealed that the economic well-being status of the household to which women belong, played a crucial role in explaining the variation in service utilization. Inequality in utilization was found to be more pronounced between the poorest and richest groups within the wealth quintiles. In adjusted models, mothers in the richest bands of wealth were 5.50 (95% confidence interval [CI]: 1.34-22.47), 2.12 (95% CI: 1.02-3.42), 4.0 (95% CI 1.58-10.10), and 2.0 (95% CI 1.02-5.88) times more likely to have assisted delivery from medically trained personnel, have institutional deliveries, and have counseling and testing for HIV/AIDS. Conclusions Association between household wealth inequality and utilization of ANC and delivery assistance from medically trained personnel, institutional delivery, and counseling and testing for HIV/AIDS suggest that higher utilization of reproductive health care services in Vanuatu poor-rich inequalities need to be addressed. Reducing poverty and making services more available and accessible to the poor may be essential for improving overall reproductive health care utilization rate in Vanuatu.